Menghadapi Krisis Lingkungan melalui Pembelajaran IPA Berbasis Education for Sustainable Development (ESD): Systematic Literature Review - Putri Rahadian Dyah Kusumawati; Arif Naufan Saputra; Milatunissa (Universitas Garut, 2026)
Environmental crises characterized by climate change, biodiversity loss, pollution, and waste have highlighted the urgent need for educational transformation to foster sustainable generations. Education for Sustainable Development (ESD) is considered a relevant approach for integration into primary science education because it connects scientific knowledge with environmental awareness and action. This study aimed to analyze the forms of implementation, impacts, and challenges of ESD integration in primary science learning. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Data were obtained from the Scopus database between 2016 and 2026 using keywords related to ESD, science education, and elementary school. Through the screening process, 11 articles met the inclusion criteria and were analyzed using a qualitative descriptive approach. The findings revealed that ESD was implemented through the integration of sustainability concepts into science lessons, outdoor learning, project-based learning, interdisciplinary approaches, sustainability-themed science stories, and the development of learning modules and digital platforms. The implementation of ESD positively influenced cognitive, affective, behavioral, and skills domains, including sustainability understanding, environmental awareness, pro-environmental behavior, critical thinking, creativity, collaboration, and reflective thinking. However, several challenges remain, including limited integration of sustainability content in curricula and teaching materials, gaps between students’ environmental attitudes and factual knowledge, and the need to strengthen teachers’ competencies. This study contributes a thematic synthesis demonstrating that ESD-based science learning in primary schools is most effective when implemented through contextual, participatory, and experiential learning approaches that promote students’ sustainability competencies.Keywords: Education for Sustainable Development, science learning, primary school, sustainability, environmental literacy